ACCELERATION OF THE ROLE OF THE KPK IN PREVENTION AND ERADICATION OF CORRUPTION CRIMINAL ACTS POST AMENDMENT TO LAW NUMBER 19 OF 2019 - Anwar Anwar; Fathur Rauzi (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The Corruption Eradication Commission in carrying out its duties and authorities is independent and free from the influence of any power. This article aims to describe the efforts of the Corruption Eradication Commission in preventing the eradication of criminal acts of corruption after the enactment of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Crime Commission. This type of research is normative legal research which is oriented to processing legal principles, legal doctrines, and current law. This research also uses primary legal materials, secondary legal materials, and tertiary legal materials. The three legal materials were collaborated in an analytical and prescriptive study in this study using a statutory and conceptual approach. The findings in this study reveal that the revised KPK Law provides convenience in enforcing the law on corruption by building synergy with other law enforcement officials such as the Indonesian National Police, the Indonesian Attorney General's Office by prioritizing prevention without ignoring the principles of eradicating corruption. In addition, the Corruption Eradication Commission's supervisory board is a state institution within the executive power cluster that carries out the task of preventing and eradicating criminal acts with a supervisory function to carry out the oversight function in the process of enforcing criminal acts of corruption committed by the Corruption Eradication Commission.